Calcium carbide related ocular burn injuries during mango ripening season of West Bengal, eastern India - Bandyopadhyay, Sabyasachi; Saha, M; Biswas, S; Ranjan, A; Naskar, AK; Bandyopadhyay, L (Nepalese Journal of Ophthalmology, 2013)
Introduction: Calcium carbide used in fruit ripening industry as a cheap alternative to natural plant hormone ethylene produces highly inflammable acetylene gas. Inadvertent ignition of this gas can cause severe ocular burn injury with unilateral or bilateral blindness. Objective: To determine the characteristics and visual outcome of ocular burn injuries from calcium carbide during mango ripening season of West Bengal, eastern India. Materials and methods: A prospective study of all cases of calcium carbide related ocular burn injury attending a tertiary care hospital during mango ripening season was carried out. The demographic features, characteristics of the injury, management and outcomes were recorded. Results: Fifty five eyes of 33 patients were studied. Males were more commonly affected (20 patients, 60.6%) than females. The injury was bilateral in 22 patients (66.66%). Seventeen patients (51.51%) were below 20 years of age. Ten eyes had open globe injuries and 45 eyes had closed globe injuries. One eye of a patient had to be enucleated (3%). Children below 14 years of age were mainly injured while playing with indigenous fireworks of shooting carbide. Middle aged women were affected particularly during ignition of evening lamps. Carbide lamp was another source of injury. Conclusion: Males are more commonly affected by calcium carbide related ocular injuries. Children and young adults are the common victims. Such injuries can involve both the eyes and cause a permanent visual disability. Nepal J Ophthalmol 2013; 5(10): 242-245 DOI: http://dx.doi.org/10.3126/nepjoph.v5i2.8736